2015
DOI: 10.4103/0366-6999.149213
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating Potential of Extraintestinal Systemic Manifestations and Colonoscopic Features in Chinese Patients with Intestinal Behçet's Disease and Crohn's Disease

Abstract: Background:The distinction between intestinal Behçet's disease (BD) and Crohn's disease (CD) is always challenging due to many overlapping clinical features. We conducted a retrospective study to reveal valuable strategies for the differential diagnosis between intestinal BD and CD in Chinese patients based on their clinical and colonoscopic features.Methods:Thirty-five intestinal BD patients and 106 CD patients hospitalized from January 1983 to January 2010, who had ulcerative lesions in the terminal ileum or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 19 publications
5
25
1
Order By: Relevance
“…However, there are many differences between intestinal BD and CD on careful analysis. Research has historically suggested that mucocutaneous lesions were the most powerful discriminating factors between the diseases (11). Our study confirmed that oral ulcers, genital ulcers, mucocutaneous lesions, and hematological disease were suggestive factors for intestinal BD on univariate analysis.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…However, there are many differences between intestinal BD and CD on careful analysis. Research has historically suggested that mucocutaneous lesions were the most powerful discriminating factors between the diseases (11). Our study confirmed that oral ulcers, genital ulcers, mucocutaneous lesions, and hematological disease were suggestive factors for intestinal BD on univariate analysis.…”
Section: Discussionsupporting
confidence: 84%
“…It is easily misdiagnosed because there are no specific pathological or laboratory markers for the diagnosis of the entity. Several case reports and clinical studies highlighted the difficulties in making this distinction (5,(10)(11)(12)(13). To date, several discriminating endoscopic findings have been reported, including round shape, five or fewer lesions, focal distribution, and absence of aphthous and cobblestone lesions as features supporting the diagnosis of intestinal BD (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of intestinal BD and its differential diagnosis from other GI diseases are of great challenge for the clinicians due to their similar manifestations, especially from Crohn’s disease (CD) with ileocolonic involvement only. Both BD and CD are chronic and relapsing diseases that present as multi‐systemic inflammation and share similar colonoscopic features . In the previous studies, the criteria for differential diagnosis mainly focused on colonoscopic findings.…”
Section: Introductionmentioning
confidence: 99%
“…Both BD and CD are chronic and relapsing diseases that present as multisystemic inflammation and share similar colonoscopic features. 10 In the previous studies, the criteria for differential diagnosis mainly focused on colonoscopic findings. Round or ellipsoid ulcers, with focal distribution, single and deep location, clear and elevated margins and the rarity of aphthous ulcers or cobblestone appearance are characteristic colonoscopic features of intestinal BD.…”
Section: Introductionmentioning
confidence: 99%